Peranan Audit Manajemen Untuk Menilai Efektivitas, Efisiensi Dan Kinerja Karyawan Sumber Daya Manusia Terhadap PT. Sarana Mentari Cemerlang Surabaya - Novia Mega Putri; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2024)
This study focuses on audit management of human resources at PT. Sarana Mentari Cemerlang Surabaya, with an emphasis on employee productivity, efficiency, and work quality. The method of data collection that is used is deskriptif, which involves gathering data through observations and wawancara. The subject of analysis is the employee of the company. The type of data that is used is qualitative, with initial data from employees and human resource management. The study's findings indicate that while the company's human resource management program has good potential, its implementation is still subpar. Programs for hiring, selection, training, and employee development turned out to be very effective, even though there is still room for improvement. Penilaian kinerja karyawan dianggap baik, notwithstanding the possibility of bias arising from a closed session. The compensation program and the JASA balas seem to be working well, but improvements are needed to raise the level of transparency and keadilan. Programs for health and safety at work are doing well, but home improvement needs to be improved. Although the work-related stress reduction program appears to be effective, it is recommended to increase employee turnover in PHK.